GS-8374, a prototype phosphonate-containing inhibitor of HIV-1 protease, effectively inhibits protease mutants with amino acid insertions - Grantz Šašková, Klára; Kozíšek, Milan; Stray, Kirsten; de Jong, Dorien; Rezáová, Pavlína; Brynda, Jirí; van Maarseveen, Noortje M; Nijhuis, Monique; Cihlár, Tomáš; Konvalinka, Jan (Journal of virology, 2014)
Insertions in the protease (PR) region of human immunodeficiency virus (HIV) represent an interesting mechanism of antiviral resistance against HIV PR inhibitors (PIs). Here, we demonstrate the improved ability of a phosphonate-containing experimental HIV PI, GS-8374, relative to that of other PIs, to effectively inhibit patient-derived recombinant HIV strains bearing PR insertions and numerous other mutations. We correlate enzyme inhibition with the catalytic activities of corresponding recombinant PRs in vitro and provide a biochemical and structural analysis of the PR-inhibitor complex.
Keywords: virová léková rezistence; Organophosphonates; lidé; sekvence aminokyselin; Humans; organofosfonáty; Binding Sites; molekulární modely; Models, Molecular; HIV-1; Crystallography, X-Ray; HIV Protease; HIV infekce; inhibitory HIV-proteasy; inzerční mutageneze; vazebná místa; Mutagenesis, Insertional; HIV Infections; HIV Protease Inhibitors; Amino Acid Sequence; Drug Resistance, Viral; HIV-proteasa; krystalografie rentgenová